2015
DOI: 10.1016/j.anr.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Living with Atrial Fibrillation: An Analysis of Patients' Perspectives

Abstract: Patients need to be provided with relevant individual training and counselling so that they lead more satisfactory lives. In addition, appropriate health appointment and monitoring systems should be developed for patients to reduce the problems associated with frequent follow-up appointments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 29 publications
(46 reference statements)
2
46
0
1
Order By: Relevance
“…The few qualitative studies that have been conducted on persons with AF reveal some illness beliefs in their results, even though they have not explicitly investigated such beliefs. In agreement, the studies of Altiok et al (2015) and McCabe et al (2011b) report the beliefs of persons with AF as expressing a need to incorporate and normalise AF into daily life.…”
Section: Previous Studies On Illness Beliefs In Afmentioning
confidence: 79%
See 2 more Smart Citations
“…The few qualitative studies that have been conducted on persons with AF reveal some illness beliefs in their results, even though they have not explicitly investigated such beliefs. In agreement, the studies of Altiok et al (2015) and McCabe et al (2011b) report the beliefs of persons with AF as expressing a need to incorporate and normalise AF into daily life.…”
Section: Previous Studies On Illness Beliefs In Afmentioning
confidence: 79%
“…, Altiok et al . ). Even though the present study also found that AF imposed limitations and restrictions on daily life, they were not regarded with profound pessimism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with AF on VKA face limitations in their activities of daily living and social lives due to frequent monitoring, clinic visits, bleeding leading to frequent hospitalizations, and lifestyle or dietary restrictions that ultimately impact health‐related QoL. Furthermore, the use of VKA for stroke prevention in patients with AF has been shown to negatively impact QoL, particularly in those of advanced age …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of VKA for stroke prevention in patients with AF has been shown to negatively impact QoL, particularly in those of advanced age. 5 Presently, the increasing number of structural cardiovascular interventions and the expected increase of the aging of the population emerges with the fundamental issue of inability to demonstrate an increase in survival as a measurement of treatment success. For the very elderly, QoL may, therefore, represent a better marker.…”
Section: Introductionmentioning
confidence: 99%